2008
DOI: 10.1016/j.neuron.2008.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory CNG Channel Desensitization by Ca2+/CaM via the B1b Subunit Affects Response Termination but Not Sensitivity to Recurring Stimulation

Abstract: Ca2+/calmodulin-mediated negative feedback is a prototypical regulatory mechanism for Ca2+-permeable ion channels. In olfactory sensory neurons (OSNs), such regulation on the cyclic nucleotide-gated (CNG) channel is considered a major mechanism of OSN adaptation. To determine the role of Ca2+/calmodulin desensitization of the olfactory CNG channel, we introduced a mutation in the channel subunit CNGB1b in mice that rendered the channel resistant to fast desensitization by Ca2+/calmodulin. Contrary to expectati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 50 publications
3
102
2
Order By: Relevance
“…In vertebrate OSNs, several mechanisms have been proposed, including the desensitization of transduction channels, phosphorylation of odorant receptors, inhibition of adenylyl cyclase, and potentiation of phosphodiesterase activity (37,38,45). Recent molecular genetic studies have revealed, however, that adaptation in vertebrate OSNs is more complex than previously understood (46,47). To date, the odor transduction mechanism in Drosophila OSNs remains unclear, although heterologous studies have suggested novel and controversial mechanisms (43).…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrate OSNs, several mechanisms have been proposed, including the desensitization of transduction channels, phosphorylation of odorant receptors, inhibition of adenylyl cyclase, and potentiation of phosphodiesterase activity (37,38,45). Recent molecular genetic studies have revealed, however, that adaptation in vertebrate OSNs is more complex than previously understood (46,47). To date, the odor transduction mechanism in Drosophila OSNs remains unclear, although heterologous studies have suggested novel and controversial mechanisms (43).…”
Section: Discussionmentioning
confidence: 99%
“…Both mouse ) and hamster (Liman 2003) VSNs express a Ca 2+ -activated nonselective cation current that might boost sensory signals. By contrast, Ca 2+ /calmodulin mediates VSN adaptation and gain control by inhibition of TRPC2 ), analogous to effective inhibition of cyclic nucleotide-gated channels in sensory neurons of the main olfactory epithelium (Bradley et al 2001(Bradley et al , 2004Munger et al 2001;Song et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mislocalization of the Ca 2+ -binding factor calmodulin, which together with Ca 2+ renders the CNG channel less sensitive to cAMP (Song et al, 2008), could lead to slowed adaptation of the response during sustained odorant exposure. Calmodulin has also been shown to modulate channel properties by activating calmodulin kinases through direct interaction with the Drosophila melanogaster PDZ protein InaD (Chevesich et al, 1997;Xu et al, 1998), and MUPP1 has been shown to bind to the calmodulin-dependent kinase CaMKII (Ackermann et al, 2009).…”
Section: Discussionmentioning
confidence: 99%